Projeto adequação de máquinas NR 12 - Scherer, Everton Mattos (Universidade do Vale do Rio dos Sinos, 2016)
This paper aims to present a project plan for the adequacy of machines in compliance with NR12 (Regulatory standard nº 12) in the company Metal Máquinas. The project will be managed by the safety area with direct support in the management of the execution of the maintenance area. The project will involve the company contracted with the Safety Engineer to make the initial reports to survey the current condition of the machines and what will be necessary to carry out the adequacy and final reports that will attest to the adequacy and compliance to NR12. The project will also have a company contracted for the production and installation of the protections and safety devices. The purpose of the project is to achieve the suitability of 5 presses, 3 aluminum injection molding machines and 3 machining centers generating project documentation and report attesting its conformity.
Keywords: NR12; Segurança de máquinas; Acidente do trabalho; Interface de segurança; Safety of machinery; Work accident; Safety interface